2017
DOI: 10.2217/pgs-2017-0147
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Role of NUDT15 Variants on Thiopurine-Induced Myelotoxicity in Asian Inflammatory Bowel Disease Patients

Abstract: These findings highlight the critical relevance of NUDT15 pharmacogenetics in predicting for thiopurine-induced myelotoxicity and confirm the lack of significance of TPMT variants in Asian inflammatory bowel disease patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 27 publications
4
41
0
Order By: Relevance
“…We revealed that platelet count was affected by the NUDT15 variant in the long‐term use of thiopurine. Consistent with our data, a previous study showed a significant decline in platelet count with increasing copy numbers of the risk T allele of NUDT15 within 4, 8, and 12 weeks and 6 months after initiating thiopurine . Conversely, Kojima et al .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We revealed that platelet count was affected by the NUDT15 variant in the long‐term use of thiopurine. Consistent with our data, a previous study showed a significant decline in platelet count with increasing copy numbers of the risk T allele of NUDT15 within 4, 8, and 12 weeks and 6 months after initiating thiopurine . Conversely, Kojima et al .…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with our data, a previous study showed a significant decline in platelet count with increasing copy numbers of the risk T allele of NUDT15 within 4, 8, and 12 weeks and 6 months after initiating thiopurine. 24 Conversely, Kojima et al addressed that platelet count did not differ significantly between wild type and mutated type of NUDT15 during 16 weeks of thiopurine administration. 23 Further studies are necessary to figure out this point.…”
Section: Discussionmentioning
confidence: 98%
“…Thirteen studies were identified that evaluated NUDT15 variants as risk factors for TIL in IBD patients, one also described the association of NUDT15 activity and TIL (Table S3). The majority of studies were performed in East‐Asian cohorts, one study included only patients of European ancestry . Studied NUDT15 variants were NUDT15 R139C (rs116855232) in 13 studies, NUDT15 c.36_37ins/delGGAGTC (rs746071566) in six studies and c.52G > A (rs186364861) in four studies.…”
Section: Resultssupporting
confidence: 62%
“…The association of TPMT genotype polymorphisms and TIL was assessed in 31 studies, the association of TPMT enzymatic activity and TIL in 12 (Table S1). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation